Analisis Pemasaran dan Pendapatan Pedagang Sapi PO Kebumen Siap Potong di Pasar Hewan Argopeni Kecamatan Kebumen Kabupaten Kebumen: Analysis of Marketing and Income of Kebumen PO Cattle Traders Ready for Slaughter at the Argopeni Animal Market Kebumen District Kebumen Regency - Ismawatun, Ismawatun; Nuraeni, Nunur (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2024)
Background: This research is to determine the income of ready-to-slaughter PO Kebumen cattle traders and their marketing flow at the Argopeni Market, Kebumen District, Kebumen Regency. Purpose: This research aims to determine the percentage of sales of ready-to-slaughter PO Kebumen cattle using blantik and without blantik services at the Argopeni Animal Market, Kebumen Regency, to determine the income of ready-to-slaughter PO Kebumen cattle traders at the Argopeni Animal Market, Kebumen Regency, and to determine the influence of the profile of PO cattle traders Kebumen ready to cut as an independent variable consisting of age, experience and education on income as the dependent variable. Methods: This research is descriptive research using a survey method using a questionnaire instrument for data collection. The sampling technique in this research used a census where the sample of PO Kebumen cattle traders ready for slaughter was 10 people. The data analysis technique used to test the hypothesis is multiple linear regression analysis. Results: The results of the variance analysis show that the variables age, experience and education have a significant effect (P>0.05) on the income of ready-to-slaughter PO Kebumen cattle traders. The marketing channel for ready-to-slaughter PO Kebumen cattle at the Argopeni Animal Market which uses blantik services is 92% and those without blantik are 8%. The average income of PO Kebumen cattle traders ready for slaughter at the Kebumen Argopeni Animal Market is IDR 28,002,000/month. Based on the Multiple R value of 0.844, it shows that there is a very strong correlation between age, experience and education and income. Conclusion: Based on the research results, it can be concluded that age, experience and education simultaneously have a correlation with the income of ready-to-slaughter PO Kebumen cattle traders at the Argopeni Animal Market.